Beyond the bulk: overview and novel insights into the dynamics of muscle satellite cells during muscle regeneration - Woo Seok Byun; Jinu Lee; Jea-Hyun Baek (BMC, 2024)
Abstract Skeletal muscle possesses remarkable regenerative capabilities, fully recovering within a month following severe acute damage. Central to this process are muscle satellite cells (MuSCs), a resident population of somatic stem cells capable of self-renewal and differentiation. Despite the highly predictable course of muscle regeneration, evaluating this process has been challenging due to the heterogeneous nature of myogenic precursors and the limited insight provided by traditional markers with overlapping expression patterns. Notably, recent advancements in single-cell technologies, such as single-cell (scRNA-seq) and single-nucleus RNA sequencing (snRNA-seq), have revolutionized muscle research. These approaches allow for comprehensive profiling of individual cells, unveiling dynamic heterogeneity among myogenic precursors and their contributions to regeneration. Through single-cell transcriptome analyses, researchers gain valuable insights into cellular diversity and functional dynamics of MuSCs post-injury. This review aims to consolidate classical and new insights into the heterogeneity of myogenic precursors, including the latest discoveries from novel single-cell technologies.